Problems of Commissioning of Technical Expert Examination of Documents - T. F. Bezsonna; L. S. Zubtsova (Law and Safety)
Certain problems that arise during the commissioning of technical expert examination of documents have been studied and analyzed. It has been clarified that they are related to the definition of the type of expert examination, the formulation of the questions to an expert regarding the objects of the examination and the preparation of materials to be examined. It has been noted that the use of special experience is needed for qualitative investigation of criminal offenses. Such experience is used in criminal proceedings in various forms. One of such forms is the commissioning of forensic examinations. One of the most common types of such examinations is technical examination of documents. It solves both diagnostic and identification issues aimed at establishing the fact of a crime, the modus operandi of a crime and the person who committed a crime. Its results are evidence in criminal proceedings.